1990
DOI: 10.1111/j.1348-0421.1990.tb00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Characterization of a Serotype 9 Human Rotavirus Strain

Abstract: A human rotavirus strain, designated AU32, that belongs to serotype 9 was isolated and was compared by RNA-RNA hybridization with recently established two serotype 9 strains (WI61 and F45) as well as other prototype human strains.These three strains exhibited a very high degree of homology with one another and shared a high degree of homology with strains belonging to the Wa genogroup but not with strains belonging to either the DS-1 or AU-1 genogroup. These results suggest that genetic constellation of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…From its first detection in 1983 until the early 1990s, serotype G9 was rarely identified globally as a cause of diarrhoea, although it was known as a common cause of asymptomatic infections in Indian neonates (Clark et al, 1987;Nakagomi et al, 1990;Urasawa et al, 1992;Zizdic et al, 1992;Das et al, 1993). Beginning in the mid-1990s, there was a remarkable increase in the detection of G9 strains as a cause of gastroenteritis and over the last 7 years or so, G9 rotaviruses have emerged as one of the most epidemiologically important strains worldwide in both developed and developing countries (Ramachandran et al, 1996;Griffin et al, 2000;Iturriza-Gó mara et al, 2000;Palombo et al, 2000;Widdowson et al, 2000;Araú jo et al, 2001;Bányai et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From its first detection in 1983 until the early 1990s, serotype G9 was rarely identified globally as a cause of diarrhoea, although it was known as a common cause of asymptomatic infections in Indian neonates (Clark et al, 1987;Nakagomi et al, 1990;Urasawa et al, 1992;Zizdic et al, 1992;Das et al, 1993). Beginning in the mid-1990s, there was a remarkable increase in the detection of G9 strains as a cause of gastroenteritis and over the last 7 years or so, G9 rotaviruses have emerged as one of the most epidemiologically important strains worldwide in both developed and developing countries (Ramachandran et al, 1996;Griffin et al, 2000;Iturriza-Gó mara et al, 2000;Palombo et al, 2000;Widdowson et al, 2000;Araú jo et al, 2001;Bányai et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Serotype G9, as the sixth recognized human VP7 specificity, was first identified during 1983 in the USA and from 1985 to 1989 in Japan, India, Yugoslavia and Thailand (Clark et al, 1987;Nakagomi et al, 1988Nakagomi et al, , 1990Urasawa et al, 1992;Zizdic et al, 1992;Das et al, 1993). Representative US and Japanese G9 strains carried P[8] VP4 specificity, possessed a 'long' electropherotype (E-type; also referred to as genome pattern or RNA profile) and, as determined by wholegenome RNA-RNA hybridization, exhibited close genomic relatedness to strain Wa (P1A[8],G1), the prototype of the most common human rotaviruses, designated the Wa genogroup (Nakagomi et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplification and cloning of the entire VP7 gene of one of the untypeable strains in our previous study revealed that the stool specimen, designated 95H115, collected in the 1994-1995 rotavirus season contained a G9 rotavirus. This G9 rotavirus represents the first re-emergence of G9 in Japan after a 9-year interval since prototype G9 strains AU32 and F45 appeared in Japan for the first time in the 1985-1986 rotavirus season (1, 16,17).…”
mentioning
confidence: 99%
“…The amplification and cloning of the entire VP7 gene of one of the untypeable strains in our previous study revealed that the stool specimen, designated 95H115, collected in the 1994-1995 rotavirus season contained a G9 rotavirus. This G9 rotavirus represents the first re-emergence of G9 in Japan after a 9-year interval since prototype G9 strains AU32 and F45 appeared in Japan for the first time in the 1985-1986 rotavirus season (1,16,17).Serotype G9 has captured global attention since the recent emergence of this serotype in India (20), the United States of America (21), Bangladesh (24), Malawi (7), Australia (19), France (2) and the United Kingdom (6). While it remains to be determined whether this global emergence of G9 strains poses a threat to the current strategy for developing rotavirus vaccines, an effort to include serotype G9 into a bovine-rotavirus UK-based reassortant vaccine, a successor to the tetravalent rhesus rotavirus vaccine (RRV-TV), has already been in progress (12).…”
mentioning
confidence: 99%